Identification and characterization of ecdysis-related neuropeptides in the lone star tick Amblyomma americanum - Lyu, Bo; Li, Jingjing; Niemeyer, Brigid; Stanley, David; Song, Qisheng (Frontiers in Endocrinology, 2023)
The lone star tick, Amblyomma americanum, is an important ectoparasite that feeds on the blood of its host and transmits diseases to humans and animals. Ecdysis-related neuropeptides (ERNs) control the behaviors necessary for arthropods to shed their outer layer of exoskeleton, although the identification and characterization of ERNs in A. americanum is still a work in progress. The present study shows that ERN catalogs (i.e., eclosion hormone, corazonin, and bursicon) are found in most arachnids, and these ERNs in A. americanum have high evolutionary relatedness with other tick species. Further analysis shows the phylogeny, sequence alignment, protein properties, and domain structures of these ERNs. Protein modeling analysis indicates that ERNs primarily consist of secondary structures and protein stabilizing forces (i.e., hydrophobic clusters, hydrogen bond networks, and salt bridges). Gene functional analysis shows that ENRs are involved in many ecdysis-related functions, including ecdysis-triggering hormone activity, neuropeptide signaling pathway, and corazonin receptor binding. Bursicon proteins have functions in chitin binding and G proteincoupled receptor activity and strong interactions with leucine-rich repeat-containing G-protein coupled receptor 5 (LGR5). Developmental and tissue-specific expression profiles indicate that ERNs were expressed in higher levels in newly molted adults and synganglia. RNAi-mediated knockdown of burs α and burs β expression led to a significant decrease in the expression of an antimicrobial peptide, defensin, suggesting they might act in signaling or regulatory pathways that control the expression of immune-related genes. Arthropods are vulnerable immediately after 2 molting because new cuticles are soft and susceptible to injury and pathogen infections. Bursicon homodimers act in prophylactic immunity during this vulnerable period by increasing the synthesis of transcripts encoding antimicrobial peptides to protect them from microbial invasion. Collectively, the expression pattern and characterization of ERNs in this study contribute to a deeper understanding of the physiological processes in A. americanum.